Developmental programing of thirst and sodium appetite. (April 2015) - Mecawi, Andre S.; Macchione, Ana F.; Nuñez, Paula; Perillan, Carmen; Reis, Luis C.; Vivas, Laura; Arguelles, Juan
Graphical abstract: Scheme showing the possible consequence of several environmental factors (lifestyle, hydromineral balance and/or challenges, neuroendocrine disturbances, dietary composition and drug use) at different stages of the developmental programing of thirst and sodium appetite, as well as the predisposition to pathological conditions such as hypertension and/or kidney damage. Highlights: We review here the ontogeny of thirst and sodium appetite. Thirst and sodium appetite are programed by the developmental environment. Hydromineral/neuroendocrine disorders and lifestyle are the main programing factors. Several neuroendocrine systems are epigenetically regulated and potentially involved. Abstract: Thirst and sodium appetite are the sensations responsible for the motivated behaviors of water and salt intake, respectively, and both are essential responses for the maintenance of hydromineral homeostasis in animals. These sensations and their related behaviors develop very early in the postnatal period in animals. Many studies have demonstrated several pre- and postnatal stimuli that are responsible for the developmental programing of thirst and sodium appetite and, consequently, the pattern of water and salt intake in adulthood in need-free or need-induced conditions. The literature systematically reports the involvement of dietary changes, hydromineral and cardiovascular challenges, renin–angiotensin system and steroid hormone disturbances, and lifestyle in these developmental factors. Therefore, this review will address how pre- and postnatal challenges can program lifelong thirst and sodium appetite in animals and humans, as well as which neuroendocrine substrates are involved. In addition, the possible epigenetic molecular mechanisms responsible for the developmental programing of drinking behavior, the clinical implications of hydromineral disturbances during pre- and postnatal periods, and the developmental origins of adult hydromineral behavior will be discussed.